THE COMPLEXITY AND ACCURACY OF NOUN PHRASES WITH MODIFIERS IN WRITTEN PRODUCTIONS OF LEARNERS OF ROMANIAN AS A FOREIGN LANGUAGE - BOCOȘ, Cristina (Studia Universitatis Babeș-Bolyai Philologia, 2017)
The Complexity and Accuracy of Noun Phrases with Modifiers in Written Productions of Learners of Romanian as a foreign language. The paper analyses the complexity and accuracy of noun phrases with modifiers in a corpus of 84 written productions by learners of Romanian as a foreign language of different L1 backgrounds. The analyzed samples are short (70-80 words), descriptive texts written by students at level A2 in Romanian. The adjective constructions present in this corpus are classified according to their complexity as well as to their typology (constructions with descriptive adjectives, with pronominal adjectives, and mixed), while their accuracy is scrutinized from two different perspectives: word order and noun-adjective agreement. A statistical analyses of the frequency of certain types of errors is offered for each group of learners that share the same linguistic background. Moreover, the data obtained from the written productions of an individual group of L1 speakers is compared to that of the others in order to highlight possible implications in teaching and assessing Romanian as a foreign language. Rezumat. Complexitatea și acuratețea grupurilor nominale cu modificatori în producțiile scrise ale vorbitorilor de limba română ca limbă străină. Lucrarea analizează complexitatea și acuratețea grupurilor nominale cu modificatori dintr-un corpus de producții scrise aparținând unor studenți de diferite origini și cu diferite limbi materne care învață româna ca limbă străină în România. Mostrele analizate sunt texte descriptive scurte (70-80 de cuvinte) scrise de studenți de nivel A2. Sintagmele adjectivale identificate la nivelul corpusului sunt clasificate în funcție de complexitatea și de tipologia lor (sintagme cu adjective propriu-zise, cu adjective pronominale și mixte). Acuratețea acestora este examinată atât din punctul de vedere al topicii, cât și din cel al acordului. Frecvența anumitor tipuri de greșeli este prezentată statistic atât la nivel global, cât și la nivelul subclaselor reprezentate de studenții care au ca limbă maternă araba, albaneza sau o limbă asiatică (= limbile materne cel mai bine reprezentate în corpus). În plus, rezultatele obținute la nivelul subclaselor anterior amintite sunt comparate între ele cu scopul de stabili posibile implicații ale limbii materne în predarea și evaluarea limbii române ca limbă străină. Cuvinte-cheie: grup nominal, modificator, adjectiv, acuratețe, complexitate, analiză statistică, limba română ca limbă străină, vorbitori de diferite origini și cu diferite limbi materne